RELATIONSHIP OF PARENTS ROLE TO CARIES INCIDENT IN ADOLESCENTS AT SUNGAI LOBAN SUBDISTRICT - Nindica Ayu Soviarini; R. Harry Dharmawan Setyawardhana; Galuh Dwinta Sari (FKG Unlam, 2022)
Background: Caries can be caused by a lack of individual knowledge about dental health and attitudes to pay attention to dental hygiene. Parents have the most important role in determining the personality, habits and behavior of the child in taking care of the teeth and mouth. Every action taken by the parents will have an influence on the character of the child. Parents who provide a positive parenting pattern to their child, will form good personality, habits and behavior towards the child. But on the contrary, parents who are less attentive and do not care will form negative personalities, habits and behaviors. Purpose: To find out relationship of parents role to caries incident in adolescents at Sungai Loban Subdistrict. Methods: This study used an observational analytic method in the form of cross-sectional research and a simple random sampling technique. The research population was grade VII students at SMP Negeri 1 Sungai Loban as many as 63 respondents. Results: The Spearman test obtained significant score results of 0.000<0.05 which means there is a correlation between the role of parents to the incidence of caries in children. The correlation value is – 0.927 and includes a very strong correlation in the negative direction (-), it can be interpreted that the relationship is opposite or if the child's caries is high then the role of parents tends to be low. Conclusion: There is a relationship of parents role to caries incident in adolescents.